Seed dormancy loss from dry after-ripening is associated with increasing gibberellin hormone levels in Arabidopsis thaliana - Nelson, Sven K.; Kanno, Yuri; Seo, Mitsunori; Steber, Camille M. (Frontiers in Plant Science, 2023)
Introduction The seeds of many plants are dormant and unable to germinate at maturity, but gain the ability to germinate through after-ripening during dry storage. The hormone abscisic acid (ABA) stimulates seed dormancy, whereas gibberellin A (GA) stimulates dormancy loss and germination. Methods To determine whether dry after-ripening alters the potential to accumulate ABA and GA, hormone levels were measured during an after-ripening time course in dry and imbibing ungerminated seeds of wildtype Landsberg erecta (Ler) and of the highly dormant GA-insensitive mutant sleepy1-2 (sly1-2). Results The elevated sly1-2 dormancy was associated with lower rather than higher ABA levels. Ler germination increased with 2-4 weeks of after-ripening whereas sly1-2 required 21 months to after-ripen. Increasing germination capacity with after-ripening was associated with increasing GA4 levels in imbibing sly1-2 and wild-type Ler seeds. During the same 12 hr imbibition period, after-ripening also resulted in increased ABA levels. Discussion The decreased ABA levels with after-ripening in other studies occurred later in imbibition, just before germination. This suggests a model where GA acts first, stimulating germination before ABA levels decline, and ABA acts as the final checkpoint preventing germination until processes essential to survival, like DNA repair and activation of respiration, are completed. Overexpression of the GA receptor GID1b (GA INSENSITIVE DWARF1b) was associated with increased germination of sly1-2 but decreased germination of wildtype Ler. This reduction of Ler germination was not associated with increased ABA levels. Apparently, GID1b is a positive regulator of germination in one context, but a negative regulator in the other.